2017
DOI: 10.4236/fns.2017.88058
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Supplementation Reduces Exercise-Induced Oxidative Stress and Increases Peak Muscular Force

Abstract: Vitamin C is a popular supplement in exercise and sport for its chemical properties i.e. antioxidant capabilities. However, no clear role has been established for vitamin C supplementation (VCS) within these areas despite nearly a century's worth of ongoing research. This study examined peak muscular pushing force (PMF) before and after a VCS intervention, 250 mg every 12 hrs for 28 days, in nine participants whom were naive to VCS and resistance exercise (RE). A dynamometer was used to perform two RE bouts, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Furthermore, in the human experiment, vitamin C supplementation suppressed the exercise-induced in VO 2 max. However, according to Evans et al [ 87 ], vitamin C supplementation is capable of increasing a peak muscular pushing force (PMF) in untrained individuals.…”
Section: Supplementation With Vitamin C and Exercise Performancementioning
confidence: 99%
“…Furthermore, in the human experiment, vitamin C supplementation suppressed the exercise-induced in VO 2 max. However, according to Evans et al [ 87 ], vitamin C supplementation is capable of increasing a peak muscular pushing force (PMF) in untrained individuals.…”
Section: Supplementation With Vitamin C and Exercise Performancementioning
confidence: 99%
“…Salivary diagnostics can also play an important role in cardiology, [147,148] for acute myocardial infarction [149]. In addition, we have previously noted that saliva analysis enables researchers to monitor the metabolic response of individuals during physical training [139,150]. Therefore, sampling saliva, plaque, and other surfaces in the oral cavity have the potential to conjure insight into distant, yet relative, organ systems, i.e., the gut.…”
Section: Salivary Biomarkers For Monitoring Health Status In the Gutmentioning
confidence: 99%
“…Bryer and Goldfarb observed that a 2-week vitamin C supplementation regimen in healthy males, followed by 4 days of eccentric exercise increased the oxidized glutathione (GSSG)/reduced glutathione (GSH) ratio, thereby preventing exercise-induced oxidative stress compared to the placebo group [ 29 ]. Evans et al reported that 28-day vitamin C supplementation increased the peak muscular pushing force and reduced exercise-induced oxidative stress [ 30 ]. Other studies have reported the positive effects of vitamin C supplementation on the reduction of exercise-induced oxidative stress [ 31 - 33 ]; however, some studies have also shown that vitamin C supplementation has no impact or even negative effects on exercise performance and training adaptations.…”
Section: Vitamin Cmentioning
confidence: 99%